What Is the Lowest Latitude of Discrete Aurorae During Superstorms? - Jeffrey J. Love; Ian R. Mann; Timo Qvick; Kalevi Mursula (Space Weather, 2025)
Abstract From a survey of published accounts of visual sightings of aurorae, a compilation is presented of the lowest identified geomagnetic latitude at which discrete aurorae were seen at local zenith during magnetic storms having intensities with maximum −Dst>200 nT. The compilation includes data for the superstorms of 2 September 1859, 4 February 1872, and 15 May 1921. A statistical model is developed representing the equatorward boundary of discrete aurorae versus storm intensity. The model indicates that a once‐per‐century storm would likely induce discrete aurorae at zenith down to a geomagnetic latitude of 34°. Insofar as aurorae can be taken as a proxy for electrojet currents, such a storm would expose many nighttime electric‐power systems in the contiguous United States or Europe to high levels of geomagnetic disturbance. A Carrington‐class storm would induce discrete aurorae down to 24°. These exposures are much greater than those indicated in recent numerical simulations of extreme magnetic storms. Using the model to infer storm intensity from reports of low‐latitude aurorae, a storm on 28 August 1859 likely had maximum −Dst=673 nT. That this storm occurred just a few days before the Carrington storm of 2 September (maximum −Dst=964 nT) deserves attention. A storm that occurred on 17 September 1770 is estimated to have had maximum −Dst=928 nT. A vision described by Ezekiel could have been inspired by aurorae from a storm with maximum −Dst=550 nT.